2011
DOI: 10.1016/s1413-8670(11)70182-9
|View full text |Cite
|
Sign up to set email alerts
|

Candida species isolated from the vaginal mucosa of HIV-infected women in Salvador, Bahia, Brazil

Abstract: Our results confirm a higher frequency of Candida spp. isolated from the vaginal mucosa of HIV-infected women and a broader spectrum of species involved. Only Candida glabrata isolates showed decreased susceptibility to fluconazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
1
4
1
Order By: Relevance
“…from the vaginal mucosa to the azole drugs commonly used in the treatment and prophylaxis of VVC 7, 8, 10, 11, 13, 22, 24, 27, 28. Concerning fluconazole, the resistance rates range from 0.8% to 12.5% 7, 10, 11, 24, 28. These values are considerably lower than the results found in our study, in which 42% of the isolates were resistant to fluconazole.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…from the vaginal mucosa to the azole drugs commonly used in the treatment and prophylaxis of VVC 7, 8, 10, 11, 13, 22, 24, 27, 28. Concerning fluconazole, the resistance rates range from 0.8% to 12.5% 7, 10, 11, 24, 28. These values are considerably lower than the results found in our study, in which 42% of the isolates were resistant to fluconazole.…”
Section: Discussioncontrasting
confidence: 83%
“…Among these, C. glabrata , described as the second most important species in cases of VVC due to its frequency10, 12, 15, 18, 23 and greater resistance to antifungals10, 22, 24 was found in 8.6% of symptomatic patients and in 14.3% of colonized patients in our study, which highlights the importance of laboratory tests for correct identification of the etiologic agent, although the clinical diagnosis of the disease is easily performed and commonly applied 2, 25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the HIV/AIDS scenario, mucosal candidiasis is one of the oldest and most common opportunistic infections in HIV-positive women [ 235 , 236 ]. Although it is not considered a syndrome-defining illness, vaginal candidiasis is classified by the centers for disease control and prevention for human immunodeficiency virus as a condition whose course or management may be altered by HIV infection [ 237 240 ].…”
Section: Immunity Of Female Genital Mucosa Hiv/aids and Stdsmentioning
confidence: 99%
“…Use of the highly active antiretroviral therapy (HAART) has extended the life span of HIV-infected persons. However, some studies have reported that even for users of this continuous therapy opportunistic infections remain a serious problem 3 , 18 . Nevertheless, to the authors' knowledge, few studies have related vaginal Candida colonization and VVC in HIV-infected women to HAART use in different populations, have enrolled relatively few HIV-infected women 15 , only treated specific clinical conditions as Candida colonization 14 , lacked appropriate matched controls 9 , 15 , or have been restricted to specialized subpopulations such as women with symptoms of vulvovaginitis 23 .…”
Section: Introductionmentioning
confidence: 99%